Insecticide-treated net ownership and utilization and factors that influence their use in Itang, Gambella region, Ethiopia: cross-sectional study - Watiro AH; Awoke W (Dove Medical Press, 2016)
Aklilu Habte Watiro,1 Worku Awoke,2 1Médecins Sans Frontières OCA (MSF Holland) Ethiopia Mission, Addis Ababa, 2Department of Epidemiology, School of Public Health, College of Medicine and Health Sciences, Bahir Dar University, Bahir Dar, Ethiopia Background: Malaria remains a major public health problem in Ethiopia. Consequently, Ethiopia designed the 2011–2015, Malaria Prevention and Control Strategic Plan to fight the vector. It was discovered that most of the studies conducted on the use of insecticide-treated nets (ITNs) were not in line with the strategic plan of the country. This study aimed to assess ITN ownership and utilization, and includes barriers related to its use among the target-area population at household (HH) level. Materials and methods: A cross-sectional design was employed in Itang for this study. Data were collected by trained nurses through face-to-face interview and observation. A total of 845 participants were selected through multistage sampling, and the size was determined by using a single-population proportion formula. EPI Info and SPSS was used for analysis, and all necessary statistical association was computed in order to explain the outcome variable through explanatory variables of this study. Results: Among 845 HHs interviewed, 81.7% (690) had at least one ITN, while 52.3% (361) had used the ITN the night preceding the data-collection day. HH awareness of malaria prevention, number of ITNs, family size, number of family members sharing sleeping area/beds, sleeping patterns of adolescents, HH-head age, and inconvenience of using ITNs were found to be barriers to the use of ITNs in this study. Conclusion and recommendation: The study concluded that very few HHs owned ITNs and there was very low usage of ITNs. In recommendation, the regional health bureau and district health office should consider bigger nets that can accommodate family members who share the same sleeping area/bed in the area. Keywords: consistent use, household, insecticide-treated nets, Itang, ownership, utilization